Enterprise risk management : a methodology for achieving strategic objectives - Monahan, Gregory, 1971- (Wiley and SAS business series., 2008)
Written for enterprise risk management (ERM) practitioners who recognize ERM's value to their organization, iEnterprise Risk Management: A Methodology for Achieving Strategic Objectives/i thoroughly examines operational risk management and allows you to leverage ERM methodology in your organization by putting author and ERM authority Gregory Monahan's Strategic Objectives At Risk (SOAR) methodology to work. A must-read for anyone interested in risk management as a strategic, value-adding tool, this no-nonsense book shows you how to use ERM and SOAR to empower your company to go from stuck to competitive. - Resumé vydavatel